Voluntary contributions with risky and uncertain marginal returns: The importance of the minimal value - Maria Vittoria Levati; Andrea Morone (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
Previous research indicates that risky and uncertain marginal returns from the public good significantly lower contributions. This paper presents experimental results illustrating that the effects of risk and uncertainty depend on the employed parameterization. Speci?cally, if the value of the marginal per capita return under the worst state of nature allows for some efficiency gains, the presence of risk and uncertainty about the public good's value is not detrimental to cooperation. This ?nding casts doubt on the hypothesis that risk and uncertainty, per se, weaken people's willingness to contribute.
Keywords: C72; C92; D81; H41; 330; Public goods experiments; Voluntary contributions; Risk; Uncertainty; Öffentliches Gut; Auktionstheorie; Unvollkommene Information; Nichtkooperatives Spiel; Risikopräferenz; Test; Theorie